Chemical characterization of inks in skin reactions to tattoo. (4th October 2022) - Colboc, Hester; Bazin, Dominique; Reguer, Solenn; Lucas, Ivan T.; Moguelet, Philippe; Amode, Reyhan; Jouanneau, Chantal; Soria, Angèle; Chasset, François; Amsler, Emmanuelle; Pecquet, Catherine; Aractingi, Sélim; et al.
Abstract : Using X‐ray fluorescence spectroscopy, X‐ray absorption spectroscopy and Raman spectroscopy, the chemical composition of inks was analyzed in a cohort of patients with cutaneous hypersensitivity reactions to tattoo. Known inorganic allergenic metals (titanium, chromium, manganese, nickel and copper) were identified in almost all cases as well as azo pigments, quinacridone, carbon black and phthalocyanine. Abstract : Skin reactions are well described complications of tattooing, usually provoked by red inks. Chemical characterizations of these inks are usually based on limited subjects and techniques. This study aimed to determine the organic and inorganic composition of inks using X‐ray fluorescence spectroscopy (XRF), X‐ray absorption spectroscopy (XANES) and Raman spectroscopy, in a cohort of patients with cutaneous hypersensitivity reactions to tattoo. A retrospective multicenter study was performed, including 15 patients diagnosed with skin reactions to tattoos. Almost half of these patients developed skin reactions on black inks. XRF identified known allergenic metals – titanium, chromium, manganese, nickel and copper – in almost all cases. XANES spectroscopy distinguished zinc and iron present in ink from these elements in endogenous biomolecules. Raman spectroscopy showed the presence of both reported (azo pigments, quinacridone) and unreported (carbon black, phtalocyanine) putative organic sensitizer compounds, and also defined the phase in which Ti was engaged. To the best of the authors' knowledge, this paper reports the largest cohort of skin hypersensitivity reactions analyzed by multiple complementary techniques. With almost half the patients presenting skin reaction on black tattoo, the study suggests that black modern inks should also be considered to provoke skin reactions, probably because of the common association of carbon black with potential allergenic metals within these inks. Analysis of more skin reactions to tattoos is needed to identify the relevant chemical compounds and help render tattoo ink composition safer.